Pengaruh FDR, NPF, ROA, CAR Terhadap Pembiayaan Mudharabah (Studi Empiris Pada Bank Umum Syariah Yang Terdaftar Di Bank Indonesia Pada Tahun 2015-2019) - Arini Wildaniyati (JAMER : Jurnal Akuntansi Merdeka, 2020)
Abstract: This study aims to determine the effect of Financing to Deposits Ratio (FDR), Non Performing Financing (NPF), Retrun On Asset (ROA), and Capital Adequacy Ratio (CAR) on Mudharabah Financing in 2015-2019 both influence partially or simultaneously . The population in this study is Sharia Commercial Banks (BUS) in Indonesia and registered with Bank Indonesia 2015-2019. The sampling method used was Purposive Sampling with certain criteria to obtain 9 Sharia Commercial Banks (BUS). This research uses quantitative methods. The independent variables in this study are Financing to Deposits Ratio (FDR), Non Performing Financing (NPF), Retrun On Asset (ROA), and Capital Adequacy Ratio (CAR). While the dependent variable in this study is Mudharabah Financing. The data analysis method used is multiple linear regression analysis and classic assumption test. The results of this study indicate that partially the Return on Asset (ROA) variable has an effect on Mudharabah Financing, while Financing to Deposits Ratio (FDR), Non Performing Financing (NPF), and Capital Adequacy Ratio (CAR) have no effect on Mudharabah Financing. Simultaneously, Financing to Deposits Ratio (FDR), Non Performing Financing (NPF), Return On Assets (ROA), and Capital Adequacy Ratio (CAR) has no effect on Mudharabah Financing in Islamic Banks in Indonesia.Keywords: Financing to Deposits Ratio (FDR), Non Performing Financing (NPF), Retrun On Asset (ROA), dan Capital Adequacy Ratio (CAR), Pembiayaan Mudharabah